Environmental and energy issues in biodiesel production using palm oil from the interspecific hybrid OxG and Elaeis guineensis: a case study in Colombia☆ - Mogollon Diego Ignacio Nieto; Venturini Osvaldo José; Batlle Eric Alberto Ocampo; González Aldemar Martinez; Munar-Florez David Arturo; Ramirez-Contreras Nidia Elizabeth; García-Nuñez Jesús Alberto; Borges Pedro Tavares; Lora Electo Eduardo Silva (Oilseeds and fats, crops and lipids, 2024)
In Colombia, in the last decade, the interspecific hybrid cultivar OxG, generated by a cross between American palm and African palm, has increased due to its tolerance to bud rot caused by Phytophthora palmivora. This study aimed to evaluate and compare the energy balance and environmental indicators of biodiesel production chains for both cultivars in Colombia. For this, an energy analysis was carried out to determine how energy is used in each process, as well as the palm energy per hectare. Also, a comparative analysis “cradle-to-gate” was made to verify the environmental performance of the genotypes studied. The functional unit was defined as 1.0 MJ of energy produced, and impacts were modeled using SimaPro v.8.0.3 software and quantified using the Impact 2002+ method. The results showed biodiesel from hybrid OxG reduced 6.2% the overall efficiency indicator of the system compared to biodiesel from E. guineensis. Life cycle CO2eq emissions of E. guineensis biodiesel were 12.5 g MJBD-1 (excluding carbon sequestration). In contrast, the CO2eq emissions of OxG hybrid biodiesel were 13.8 g MJBD-1. The life cycle efficiency indicators for biodiesel produced from OxG and E. guineensis showed a reduction in the fossil energy index of 26.9% and 19.7%, respectively.